EFFECT OF POTASH FERTILIZATION AND FOLIAR APPLICATION OF IRON AND ZINC ON GROWTH TRAITS OF TWO GENOTYPES OF MUNG BEAN - & Al-Jumaily, Abdalgafor (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted in Ehssayvillage-Amria-Fallujah district in Al-Anbar governorate during the spring season of 2012 and 2013 in order to study the effect of potassium fertilizer and foliar nutrition of iron and zinc in growth traits of two mung bean (Vigna radiata L.) genotypes. Factorial arrangement was used in RCBD with three replicates.The experiment included three levels of potassium (0, 60 and 120) kg K.ha-1, four treatments of foliar application of zinc and iron  (0, Fe150, Zn100 and Fe150 + Zn100) mg.L-1 and two mung bean genotype (Local and indian VC6089A10) .The local genotype gave the highest rate of number of leaves per plant(38.26 and27.73) leaf.plant-1, leaf area(18.62 and18.57) dm2.plant-1 and biological yield( 2.62 and  2.21) t.ha-1 for the two seasons respectively , while the indian genotype gave the highest rate of plant height (50.34 and 52.20) cm and also gave the lowest number of days from planting to maturity of pods for both seasons respectively. The level 60 kg K.ha-1 record the highest rate of plant height, number of leaves per plant , leaf area(16.57and16.05) dm2.plant-1 and biological yield(2.89and (2.17t.ha-1 for the two seasons respectively, while level 120 kg K.ha-1 gave the highest rate of the number of branches per plants(6.7and 4.86) branches.plant-1 and also gave the lowest number of days from planting to maturity of pods for both seasons respectively . So the concentration (Fe150 + Zn100) mg.L-1 from the foliar nutrition of iron and zinc gave highest rate of plant height(48.38)cm, number of branches per plants (6.47) branches.plant-1  and leaf area(14.91) dm2.plant-1 for the first seasons only . The interaction between local genotype with 60 kg K.ha-1gave the heighest rate of number of leaves per plant and leaf area(22.57  and 21.34) dm2.plant-1  for two seasons respectively .So the interaction between local genotype and concentration (Fe150+Zn100) mg.l-1 gave the highest rate of leaf area for the first seasons only. The interaction between the level 60 kg K.ha-1 of potassium and the concentration  Fe150  mg.l-1 from the foliar nutrition of iron showed significant superiority in leaf area (18.97 and 19.30) dm2.plant-1 for both seasons respectively.So the triple interaction between local genotype with level 60 kg K.ha-1 of potassium and concentration (Fe 150+  Zn 100)mg.l-1 from foliar nutrition of iron and  zinc (V1K1F3) was significant effect in number of leaves per plant and leaf area for both seasons.